Exploring the binding mechanism of PF-07321332 SARS-CoV-2 protease inhibitor through molecular dynamics and binding free energy simulations - Ahmad, Bilal; Batool, Maria; Ain, Qurat Ul; Kim, Moon Suk; Choi, Sangdun (International Journal of Molecular Sciences, 2021)
The novel coronavirus disease, caused by severe acute respiratory coronavirus 2 (SARS- CoV-2), rapidly spreading around the world, poses a major threat to the global public health. Herein, we demonstrated the binding mechanism of PF-07321332, α-ketoamide, lopinavir, and ritonavir to the coronavirus 3-chymotrypsin-like-protease (3CLpro) by means of docking and molecular dynamic (MD) simulations. The analysis of MD trajectories of 3CLpro with PF-07321332, α-ketoamide, lopinavir, and ritonavir revealed that 3CLpro–PF-07321332 and 3CLpro–α-ketoamide complexes remained stable compared with 3CLpro–ritonavir and 3CLpro–lopinavir. Investigating the dynamic behavior of ligand–protein interaction, ligands PF-07321332 and α-ketoamide showed stronger bonding via making interactions with catalytic dyad residues His41–Cys145 of 3CLpro. Lopinavir and ritonavir were unable to disrupt the catalytic dyad, as illustrated by increased bond length during the MD simulation. To decipher the ligand binding mode and affinity, ligand interactions with SARS-CoV-2 proteases and binding energy were calculated. The binding energy of the bespoke antiviral PF-07321332 clinical candidate was two times higher than that of α-ketoamide and three times than that of lopinavir and ritonavir. Our study elucidated in detail the binding mechanism of the potent PF-07321332 to 3CLpro along with the low potency of lopinavir and ritonavir due to weak binding affinity demonstrated by the binding energy data. This study will be helpful for the development and optimization of more specific compounds to combat coronavirus disease.
Keywords: Antiviral Agents; Catalytic Domain; Coronavirus 3C Proteases; Coronavirus Protease Inhibitors; COVID-19; Humans; Lactams; Leucine; Lopinavir; Molecular Docking Simulation; Molecular Dynamics Simulation; Nitriles; Proline; Ritonavir; SARS-CoV-2; 3CL protease; COVID-19; Main protease; PF-07321332; SARS-CoV-2; α-ketoamide